Predictors of site choice and eventual learning experiences in a decentralised training programme designed to prepare medical students for careers in underserved areas in South Africa - Moise Muzigaba; Keshena Naidoo; Andrew Ross; Nisha Nadesan-Reddy; Sandy Pillay (African Journal of Health Professions Education, 2016)
Background. There is a dire need for medical schools in South Africa to train medical doctors who have the capacity and willingness to work in primary healthcare facilities, particularly in rural areas. Objectives. To assess the effect of students’ gender, race, place of birth and place of high school completion on their choice of training site location and to assess the extent to which the training programme enhanced students’ learning experiences relevant to primary care across training sites.Methods. A survey design involving six cohorts of 4th-year undergraduate medical students (N=187) who were part of the 2013 Family Medicine rotation at the Nelson R Mandela School of Medicine. Self-administered questionnaires were completed by students at the end of each rotation. Data analyses involved descriptive computations and inferential statistical tests, including non-parametric tests for group comparison and generalised polynomial logistic regression. Results. Students believed that their knowledge and skills relevant to primary care increased after the rotation (p<0.0001). There were statistically significant differences between rural and urban sites on certain measures of perceived programme effectiveness. Male students were less likely to choose urban sites. Black students were less likely to choose rural sites compared with their white and Indian counterparts, as were students who attended rural high schools (odds ratio (OR) 9.3; p<0.001). Students from a rural upbringing were also less likely to choose rural sites (OR 14; p<0.001).Conclusion. Based on the findings, an objective approach for student allocation that considers students’ background and individual-level characteristics is recommended to maximise learning experiences.